Economic assessment of plantations for rubberwood production - Hassan J; Ahmad S; Arshad N L; Haron N (In: Ensuring sustainability and competitiveness of the NR industry: Proceedings of the RRIM Rubber Growers Conference, Kuala Lumpur, 1995; p361-374)
Traditionally, rubber trees are planted for the latex they produce. Wood extracted at the end of the latex exploitation period is considered a residual resource. The increasing foreign demand for rubberwood products and subsequently increased demand for the raw material by the rapidly growing domestic rubberwood industries call for concerted efforts towards establishing plantations for wood extraction. With wood resource becoming increasingly important, clones, planting density, silviculture and other agro-management practices have to be re-examined. Several alternative options of growing rubber trees solely for wood as well as wood and latex are considered. The alternatives vary in planting cycles, planting densities, latex exploitation periods and silviculture. The rationale behind consideration of various options stems from the fact that different planting cycles, period and timing of latex and wood extraction and planting densities affect both latex and log volume. Lower planting density tends to increase girthing but does not encourage growth in bole height. This and the planting density at harvest affect log volume and revenue per hectare. The timing of latex extraction and stand at the time of tapping also affect both yield per hectare. Latex extraction adversely affects girthing rate and hence log volume per tree. Results from financial analyses carried out on the various options indicated that options involving both latex and wood extraction provided higher net returns compared to those involving only wood extraction. This is attributed primarily to latex being the major revenue contributor providing more than 80;of total revenue. The most promising option appeared to be that of a 15-year planting cycle, planted with an initial density of 700 trees, 8 years untapped and 7 years latex exploitation prior to long harvesting. The option, assuming a 2000-hectare estate, has a computed NPV of RM6.4 million, an IRR of 16.6;and a B/C ratio of 1.3. Where only wood is extracted, the option found viable is that which follows more closely to that of forest silviculture. The recommended cycle is 15 years, with an initial planting density of 1000 trees/ha. Thinning is carried out deliberately to a final stand of 427 trees in the 5th and 6th year to encourage girthing. In the absence of latex and with wood being an end-period resource, the computed NPV, although positive is only RM0.5 million for a 2000-hectare estate at the assumed ex-farm log price of RM45/m3. The IRR at 10.6;is only 0.6;above the cost of capital. The computed B/C ratio was approximately 1.1. If future ex-farm log price were to increase to RM60/m3 or RM70/m3 the IRR is expected to increase to 14.3;and 16.3;providing an NPV of RM45 and RM7.2 million, respectively. At these prices, the B/C ratio is expected to increase to 1.4 and 1.6, respectively. One important assumption made in the study is that the estate sector sells their wood as green logs. If downstream processing of green logs into sawn timber or fibreboard is undertaken, the value added could be considerable. Future investments in rubber must consider shorter periods of investment cycles for both wood and latex extraction. Planters should cease to look at rubberwood as a residual resource and go downstream into wood processing activities to take advantage of the value added in rubberwood-based products. At the same time, the choice of clones for future planting must consider the potential log volume to maximise investment returns.
Keywords: Rubberwood production